ChemInform Abstract: Oxidation of Enol Acetate of Flavanone with Thallium(III) Nitrate or Phenyliodonium Diacetate: A Convenient New Route to Isoflavone and Flavone. Issue 43 (21st October 2014) - Nemeth, Istvan; Kiss‐Szikszai, Attila; Gulacsi, Katalin; Mandi, Attila; Komaromi, Istvan; Kurtan, Tibor; Antus, Sandor
Abstract The oxidation of enol acetate of flavone (I) results in the formation of two products whereas, the ratio of flavone (II) and isoflavone (III) strongly depends on the reaction conditions used.